Cognitive training improves the disturbed behavioral architecture of schizophrenia-like rats, "Wisket" - Horváth Gyöngyi (PHYSIOLOGY & BEHAVIOR, 2018)
Translational schizophrenia research depends on the relevance of animal models supported by reliable tests. Human data suggest that the intensive cognitive training in schizophrenia improves the memory impairments and decreases the chance of acute psychiatric remission. Here we examined the effects of a 10-day long training session in the behavioral architecture of a new schizophrenia-like rat substrain (Wisket) in a narrow square corridor with food rewards (AMBITUS). The instrument was designed to model the natural environment of rats and enable the simultaneous recording of multiple behavioral parameters. For the compact visualization of differences between the Wisket and control animals in several parameters (behavioromics), color-coded grid plots were applied. The Wisket animals exhibited an altered pattern and/or amount of locomotion, exploratory and food collecting activity at the first few days, revealing impaired motivation, attention, anxiety and learning ability (face validity). Most of the parameters normalized with training, except for the decreased exploratory activity. This resembles the effects of cognitive behavioral therapy in human schizophrenics providing a significant support for the predictive validity of this substrain as an animal model of schizophrenia. This study also highlights the importance of behavior tests that investigate the egocentric learning ability during reward-based tasks.